(untitled) (International Seven Journal of Multidisciplinary, 2025)
This study analyzes the definition, concepts, and tools of Applied Behavior Analysis (ABA) in the diagnosis and treatment of Autism Spectrum Disorder (ASD), with an emphasis on evidence-based practices. Using a qualitative bibliographic methodology, national and international literature was reviewed to identify effective instruments, explore their applications, and assess their impact on patients’ quality of life. Instruments such as the ADI-R, ADOS, and CARS demonstrated high diagnostic accuracy and a significant contribution to the early detection of ASD, while ABA stood out for its ability to modify behaviors and promote functionality and social integration. The results indicate that the application of validated protocols and systematic interventions can fill gaps in diagnosis and treatment, especially in the Brazilian context. It is concluded that advancing professional training and local validation of tools is essential to ensure more precise and inclusive interventions, reinforcing the importance of an interdisciplinary and personalized approach in the care of individuals with ASD.